EVA waterproof material as well as preparation method and application thereof

By adding linear low-density polyethylene and tetrafluoroethylene-ethylene copolymer with a specific average particle size to the EVA waterproof material, the problems of aging and poor processing performance of the material under high temperature environment are solved, and good mechanical properties, heat resistance and flatness are achieved.

CN119875236APending Publication Date: 2025-04-25CHENGDU KINGFA SCI & TECH ADVANCED MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510083207.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing EVA waterproof materials are prone to deform and aging in high temperature environments, resulting in waterproofing aging and poor processing performance.

Method used

A combined material including ethylene-vinyl acetate copolymer, linear low-density polyethylene and tetrafluoroethylene-ethylene copolymer was used, and prepared by melt extrusion granulation process to control the average particle size of the tetrafluoroethylene-ethylene copolymer ≤6 μm.

Benefits of technology

It improves the mechanical properties, heat resistance and flatness of EVA waterproof materials, solves the aging problem of materials in high temperature environments, and improves the processing performance of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides an EVA waterproof material and a preparation method and application thereof, and belongs to the technical field of waterproof materials. The EVA waterproof material disclosed by the invention is prepared from the following components in parts by weight: 18 to 30 parts of ethylene-vinyl acetate copolymer, 40 to 70 parts of linear low-density polyethylene and 5 to 15 parts of functional resin, the functional resin is a tetrafluoroethylene-ethylene copolymer, and the average particle size of the tetrafluoroethylene-ethylene copolymer is less than or equal to 6 microns. The linear low-density polyethylene and the tetrafluoroethylene-ethylene copolymer with the specific average particle size are added into the EVA waterproof material, so that the mechanical property, the heat resistance and the smoothness of the EVA waterproof material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of waterproof materials, and in particular to an EVA waterproof material and a preparation method and application thereof. Background Art

[0002] EVA waterproof layer is a waterproof barrier material modified with polyethylene and ethylene-vinyl acetate copolymer. It is mainly used in road or railway tunnels, subways, culverts, and building roof waterproofing. In railway tunnel applications, its product performance indicators should comply with the technical requirements of the railway industry standard TB / T3360.1-2014 of the People's Republic of China. The standard requires that the VA content should not be less than 5%.

[0003] EVA is made of ethylene and vinyl acetate copolymers. Compared with polyethylene, due to the introduction of vinyl acetate monomers in the molecular chain, the crystallinity is reduced, the flexibility and impact properties are improved, but the temperature resistance is reduced. my country's geographical environment is complex and changeable, and the corresponding materials are subject to changeable working conditions in different regions. In the western region of my country, the section from Sichuan to Tibet is located in a plateau area with a high altitude and an active crust. In some areas, it may be subjected to a high temperature (geothermal temperature of 50-80°C). The EVA waterproof material has a low thermal deformation temperature and is easy to deform. At the same time, high temperature will accelerate the aging of the material. Long-term aging will cause the material to age and become brittle, resulting in waterproofing aging. Therefore, it is necessary to provide an EVA waterproof material with high mechanical properties, heat resistance and flatness. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide an EVA waterproof material and a preparation method and application thereof.

[0005] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: an EVA waterproof material is provided, comprising the following components in parts by weight: 18-30 parts of ethylene-vinyl acetate copolymer, 40-70 parts of linear low-density polyethylene, and 5-15 parts of functional resin; the functional resin is tetrafluoroethylene-ethylene copolymer, and the average particle size of the tetrafluoroethylene-ethylene copolymer is ≤6μm.

[0006] In some embodiments, the linear low density polyethylene is a metallocene linear low density polyethylene.

[0007] In some embodiments, the linear low density polyethylene has a melt flow rate of ≤5 g / 10 min at 190° C. and 2.16 kg.

[0008] In some embodiments, the melt flow rate of the ethylene-vinyl acetate copolymer at 190° C. and 2.16 kg is ≤7 g / 10 min.

[0009] In some embodiments, the content of vinyl acetate in the ethylene-vinyl acetate copolymer is 14-40 wt %.

[0010] In some embodiments, the EVA waterproof material further comprises 0.5-1 parts by weight of an antioxidant.

[0011] In some embodiments, the antioxidant is a hindered phenol antioxidant and / or a phosphite antioxidant.

[0012] On the other hand, a method for preparing the EVA waterproof material is provided, comprising the following steps: uniformly mixing the components in proportion, and then melt-extruding and granulating to obtain the EVA waterproof material.

[0013] In some embodiments, the temperature of the melt extrusion is 180-210°C.

[0014] On the other hand, the invention provides the use of the EVA waterproof material in preparing a waterproof layer.

[0015] Compared with the prior art, the beneficial effects of the present invention are as follows: the present application adds linear low-density polyethylene and tetrafluoroethylene-ethylene copolymer with a specific average particle size to the EVA waterproof material, and the tetrafluoroethylene-ethylene copolymer is added to the EVA waterproof material in a filling manner, which can solve the processing problems of ethylene-vinyl acetate copolymer, linear low-density polyethylene and tetrafluoroethylene-ethylene copolymer, and the ethylene flexible chain segment in the tetrafluoroethylene-ethylene copolymer has a certain compatibility with the ethylene-vinyl acetate copolymer and the linear low-density polyethylene molecular chain, thereby improving the compatibility of the system, so that the EVA waterproof material has good mechanical properties, heat resistance and flatness. DETAILED DESCRIPTION

[0016] In order to facilitate understanding of the present disclosure, the present disclosure will be described more fully below. However, the present disclosure can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present disclosure more thorough and comprehensive.

[0017] As used herein:

[0018] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0019] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0020] When amount, concentration or other value or parameter is represented by range, preferred range or a series of upper preferred value and lower preferred value, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value and any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when disclosing range "1-5", described range should be interpreted as including range "1-4", "1-3", "1-2", "1-2 and 4-5", "1-3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the range is intended to include its end value and all integers and fractions within the range.

[0021] In these examples, parts and percentages are by mass unless otherwise indicated.

[0022] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0023] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0024] In order to solve the problems of poor mechanical properties, heat resistance and flatness of EVA waterproof materials in the prior art, the present disclosure provides an EVA waterproof material, comprising the following components in parts by weight: 18-30 parts of ethylene-vinyl acetate copolymer, 40-70 parts of linear low-density polyethylene, and 5-15 parts of functional resin; the functional resin is tetrafluoroethylene-ethylene copolymer, and the average particle size of the tetrafluoroethylene-ethylene copolymer is ≤6μm.

[0025] In the present disclosure, linear low-density polyethylene and tetrafluoroethylene-ethylene copolymer are added to the EVA waterproof material. Since the melting point of tetrafluoroethylene-ethylene copolymer is high, when the tetrafluoroethylene-ethylene copolymer is processed at the melting point, the ethylene-vinyl acetate copolymer and the linear low-density polyethylene will decompose, resulting in a decrease in the overall performance of the EVA waterproof material. If the processing is carried out within the processing temperature range of the ethylene-vinyl acetate copolymer and the linear low-density polyethylene, the tetrafluoroethylene-ethylene copolymer cannot melt. The applicant has found that the tetrafluoroethylene-ethylene copolymer with an average particle size of ≤5 μm is selected and added to the EVA in the form of a filler. A waterproof material can solve the problem of simultaneous processing of ethylene-vinyl acetate copolymer, linear low-density polyethylene and tetrafluoroethylene-ethylene copolymer, and the ethylene flexible chain segment in tetrafluoroethylene-ethylene copolymer has a certain compatibility with the ethylene-vinyl acetate copolymer and linear low-density polyethylene molecular chain, which improves the compatibility of the system and makes the EVA waterproof material have good mechanical properties, heat resistance and flatness; if the average particle size of the tetrafluoroethylene-ethylene copolymer is greater than 6μm, the tetrafluoroethylene-ethylene copolymer is difficult to disperse in the EVA waterproof material, which greatly reduces the tensile properties and flatness of the EVA waterproof material.

[0026] For example, in different embodiments, the weight proportions of ethylene-vinyl acetate copolymer may be, but are not limited to, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, or 30 parts.

[0027] Specifically, the standard TB / T 3306.1-2014 stipulates that the VA content of EVA waterproof material should not be less than 5%.

[0028] For example, in different embodiments, the weight proportion of the linear low density polyethylene may be, but is not limited to, 40 parts, 42 parts, 45 parts, 47 parts, 50 parts, 53 parts, 55 parts, 58 parts, 60 parts, 63 parts, 65 parts, 68 parts, and 70 parts.

[0029] For example, in different embodiments, the weight proportion of tetrafluoroethylene-ethylene copolymer may be, but is not limited to, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15 parts.

[0030] For example, in different embodiments, the average particle size of tetrafluoroethylene-ethylene copolymer can be but is not limited to 0.1 μm, 0.3 μm, 0.5 μm, 0.8 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.2 μm, 4.4 μm, 4.6 μm, 4.8 μm, 5 μm, 6 μm.

[0031] Specifically, the average particle size of tetrafluoroethylene-ethylene copolymer is obtained by testing according to GB / T 19077-2016 standard.

[0032] The method for controlling the average particle size of tetrafluoroethylene-ethylene copolymer in the present disclosure is not limited. For example, the average particle size of tetrafluoroethylene-ethylene copolymer can be controlled by crushing, grinding or screening. If the average particle size of tetrafluoroethylene-ethylene copolymer is not within the range of the present disclosure after a single crushing or grinding, multiple crushing or grinding can be performed until the average particle size of tetrafluoroethylene-ethylene copolymer reaches the desired range.

[0033] Specifically, the steps of grinding tetrafluoroethylene-ethylene copolymer are as follows:

[0034] The tetrafluoroethylene-ethylene copolymer is added into a container containing liquid nitrogen, and allowed to stand for 5-10 minutes, and then transferred into a grinding machine for grinding. The ground material is sieved to obtain a first powder with an average particle size of 270-830 μm;

[0035] The first powder is added into a container containing liquid nitrogen, and after standing for 5-10 minutes, it is transferred into a grinding machine and ground into a desired average particle size.

[0036] The use of linear low-density polyethylene in the waterproof material of this application can obtain excellent tensile strength, elongation, Vicat softening point and flatness. If other types of polyethylene are used, such as ordinary low-density polyethylene or high-density polyethylene, the above properties cannot be taken into account.

[0037] In some embodiments, the linear low density polyethylene is a metallocene linear low density polyethylene.

[0038] The applicant has found that metallocene linear low-density polyethylene can further improve the mechanical properties of EVA waterproof materials.

[0039] In some embodiments, the melt flow rate of the linear low density polyethylene at 190°C and 2.16kg is ≤5g / 10min; for example, it can be but not limited to 0.1g / 10min, 0.5g / 10min, 1g / 10min, 1.5g / 10min, 2g / 10min, 2.5g / 10min, 3g / 10min, 4g / 10min, 4.5g / 10min, 5g / 10min, and the test standard is GB / T3682.1-2018.

[0040] In some embodiments, the melt flow rate of the ethylene-vinyl acetate copolymer at 190°C and 2.16kg is ≤7g / 10min; for example, it can be but not limited to 0.1g / 10min, 0.5g / 10min, 1g / 10min, 2g / 10min, 3g / 10min, 4g / 10min, 5g / 10min, 6g / 10min, 6.5g / 10min, 7g / 10min, and the test standard is GB / T3682.1-2018.

[0041] In some embodiments, the content of vinyl acetate in the ethylene-vinyl acetate copolymer is 14-40wt%; for example, it can be but not limited to 14wt%, 18wt%, 22wt%, 26wt%, 28wt%, 32wt%, 36wt%, 40wt%.

[0042] Specifically, the vinyl acetate content in the ethylene-vinyl acetate copolymer is tested according to ISO 8985-2022.

[0043] In some embodiments, the EVA waterproof material further comprises 0.5-1 parts by weight of an antioxidant.

[0044] For example, in different embodiments, the weight portion of the antioxidant may be, but is not limited to, 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part, or 1 part.

[0045] In some embodiments, the antioxidant is a hindered phenol antioxidant and / or a phosphite antioxidant.

[0046] Specifically, the antioxidant is a mixture of antioxidant 1010 and antioxidant 168, and the mass ratio of antioxidant 1010 to antioxidant 168 is 1-2:1.

[0047] On the other hand, a method for preparing the EVA waterproof material is provided, comprising the following steps: uniformly mixing the components in proportion, and then melt-extruding and granulating to obtain the EVA waterproof material.

[0048] Specifically, the mixing speed is 300-500r / min, and the mixing time is 1-2min;

[0049] The above speed and mixing time are not limited, and the final intermediate material can be mixed evenly. Adjust the process parameters according to the situation;

[0050] Specifically, the temperature of the melt extrusion is 180-210°C.

[0051] On the other hand, the invention provides the use of the EVA waterproof material in preparing a waterproof layer.

[0052] In order to further illustrate the present invention, the EVA waterproof material provided by the present invention and its preparation method and application are described in detail below in conjunction with embodiments, but they should not be understood as limiting the scope of protection of the present invention.

[0053] The raw materials used in the embodiments and comparative examples are described below, but are not limited to these materials:

[0054] Ethylene-vinyl acetate copolymer: vinyl acetate content is 27wt%, melt flow rate is 7g / 10min at 190℃ and 2.16kg, EVA6020M, Yulin Petrochemical;

[0055] Polyethylene 1: Linear low-density polyethylene prepared by Ziegler-Natta catalyst, melt flow rate of 3.5 g / 10 min at 190 °C and 2.16 kg, LLDPE 3518PA, ExxonMobil;

[0056] Polyethylene 2: Linear low-density polyethylene prepared by metallocene catalyst, melt flow rate of 1 g / 10 min at 190 °C and 2.16 kg, LLDPE 1018MA, ExxonMobil;

[0057] Polyethylene 3: high-density polyethylene, melt flow rate at 190°C, 2.16 kg is 0.3 g / 10 min, HDPE 5502, Maoming Petrochemical;

[0058] Functional resin 1: tetrafluoroethylene-ethylene copolymer, average particle size 2 mm, purchased from Asahi Glass, Japan, fluon730AP;

[0059] Functional resin 2: Homemade, the preparation method is:

[0060] S1: Add the functional resin 1 into a container containing liquid nitrogen, let it stand for 5 minutes, then transfer it to a grinder and grind it for 3 minutes. The ground material is sieved to obtain a first powder with an average particle size of 500 μm;

[0061] S2: adding the first powder into a container filled with liquid nitrogen, allowing it to stand for 10 minutes, transferring it to a grinder and grinding it for 20 minutes to obtain a functional resin 2 with an average particle size of 3.2 μm;

[0062] Functional resin 3: self-made, the preparation method thereof is different from that of functional resin 2 in that the grinding time in step 2 is 15 min, and the average particle size of the obtained functional resin 3 is 5.1 μm;

[0063] Functional resin 4: self-made, the preparation method thereof is different from that of functional resin 2 in that the grinding time in step 2 is 10 min, and the average particle size of the obtained functional resin 5 is 10 μm;

[0064] Functional resin 5: Homemade, the preparation method is:

[0065] The tetrafluoroethylene-hexafluoropropylene copolymer was added into a container containing liquid nitrogen, allowed to stand for 8 minutes, and then transferred to a grinder for grinding for 3 minutes. The ground material was sieved to obtain a first powder with an average particle size of 500 μm; wherein the tetrafluoroethylene-hexafluoropropylene copolymer was purchased from Daikin, Japan, NP-20, with an average particle size of 3 mm;

[0066] S2: adding the first powder into a container filled with liquid nitrogen, leaving it to stand for 10 minutes, transferring it to a grinder and grinding it for 12 minutes to obtain a functional resin 5 with an average particle size of 4.8 μm;

[0067] Functional resin 6: Homemade, the preparation method is:

[0068] The polytetrafluoroethylene was added into a container containing liquid nitrogen, allowed to stand for 2 minutes, and then transferred to a grinder for grinding for 3 minutes. The ground material was sieved to obtain a first powder with an average particle size of 500 μm. The polytetrafluoroethylene was purchased from Asahi Glass of Japan with a brand of L;

[0069] S2: adding the first powder into a container filled with liquid nitrogen, allowing it to stand for 10 minutes, transferring it to a grinder and grinding it for 12 minutes to obtain a functional resin 6 with an average particle size of 4.9 μm;

[0070] Antioxidants: Antioxidant 1010 and Antioxidant 168. The mass ratio of Antioxidant 1010 to Antioxidant 168 is 1:1. Antioxidant 1010 and Antioxidant 168 are both purchased from BASF.

[0071] Examples and Comparative Examples

[0072] The components of the EVA waterproof material of the embodiment and comparative example are shown in Table 1; the preparation method thereof comprises the following steps:

[0073] After uniformly mixing the components according to Table 1, the obtained mixture is added to a twin-screw extruder for melt extrusion granulation to obtain an EVA waterproof material; wherein the aspect ratio of the twin-screw extruder is 40:1, the screw speed is 400 rpm, and the extrusion temperature is 180-210°C.

[0074] The EVA waterproof materials obtained in the examples and comparative examples were subjected to performance tests, and the test methods were as follows:

[0075] (1) Tensile strength and elongation at break: tested in accordance with GB / T 528, type 5 specimens, tensile rate 250 mm / min;

[0076] (2) Vicat softening point: tested according to the A120 method in standard GB / T 1633-2000;

[0077] (3) Flatness: The EVA waterproof materials obtained in the examples and comparative examples were extruded through a cast film extruder to obtain sheets with a thickness of 1.5 mm, which were cut into samples of 50*50*1.5 mm. The samples were placed on a horizontal ground and the contact angle between the sample and the horizontal ground was tested. The smaller the contact angle, the better the flatness of the EVA waterproof material.

[0078] The test results are shown in Table 1.

[0079] Table 1

[0080]

[0081]

[0082] From the experimental data in Table 1, it can be seen that the tensile strength of the EVA waterproof material disclosed in the present invention is 27.5-32.8 MPa, the elongation is 845-945%, the Vicat softening point is 98-114°C, and the contact angle between the sample and the horizontal ground is 2-6°.

[0083] By comparing Examples 3-4 and Comparative Example 1, it can be seen that when the polyethylene is linear low-density polyethylene, the tensile strength of the obtained EVA waterproof material is 30.9-32.8 MPa, the elongation is 933-945%, the Vicat softening point is above 108°C, and the contact angle between the sample and the horizontal ground is below 4°, indicating that compared with high-density polyethylene, linear low-density polyethylene can further improve the mechanical properties and flatness of the EVA waterproof material.

[0084] By comparing Example 3 with Examples 5-8, it can be seen that when the weight proportion of the functional resin is 8-12 parts, the tensile strength of the obtained EVA waterproof material is 29.4-30.9 MPa, the elongation is 908-933%, the Vicat softening point is 106-112°C, and the contact angle between the sample and the horizontal ground is 2.5-3.5°, indicating that when the weight proportion of the functional resin is 8-12 parts, the overall performance of the obtained EVA waterproof material is better.

[0085] By comparing Example 3, Example 9 and Comparative Examples 3-4, it can be seen that when the average particle size of the functional resin is ≤6μm, the tensile strength of the obtained EVA waterproof material is 29-31MPa, the elongation is 885-933%, the Vicat softening point is 100-110°C, and the contact angle between the sample and the horizontal ground is 2-6°, indicating that the average particle size of the functional resin is ≤5μm, which can further improve the mechanical properties of the EVA waterproof material.

[0086] By comparing Example 3 and Comparative Examples 5-6, it can be seen that when the functional resin is tetrafluoroethylene-ethylene copolymer, the tensile strength of the obtained EVA waterproof material is 30.9 MPa, the elongation is 933%, the Vicat softening point is 108°C, and the contact angle between the sample and the horizontal ground is 2.6°, indicating that compared with tetrafluoroethylene-hexafluoropropylene copolymer or polytetrafluoroethylene, tetrafluoroethylene-ethylene copolymer can significantly improve the mechanical properties, heat resistance and flatness of EVA waterproof materials.

[0087] Finally, it should be noted that the above embodiments are used to illustrate the technical solution of the present disclosure rather than to limit the protection scope of the present disclosure. Although the present disclosure has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present disclosure can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present disclosure.

Claims

1. An EVA waterproof material, characterized in that: The invention comprises the following components in parts by weight: 18-30 parts of ethylene-vinyl acetate copolymer, 40-70 parts of linear low-density polyethylene and 5-15 parts of functional resin; the functional resin is tetrafluoroethylene-ethylene copolymer, and the average particle size of the tetrafluoroethylene-ethylene copolymer is ≤6μm.

2. The EVA waterproof material according to claim 1, characterized in that: The linear low density polyethylene is metallocene linear low density polyethylene.

3. The EVA waterproof material according to claim 1, characterized in that: The linear low-density polyethylene has a melt flow rate of ≤5 g / 10 min under the conditions of 190° C. / 2.16 kg.

4. The EVA waterproof material according to claim 1, characterized in that: The melt flow rate of the ethylene-vinyl acetate copolymer at 190° C. and 2.16 kg is ≤7 g / 10 min.

5. The EVA waterproof material according to claim 1, characterized in that: The content of vinyl acetate in the ethylene-vinyl acetate copolymer is 14-40wt%.

6. The EVA waterproof material according to claim 1, characterized in that: The EVA waterproof material also includes 0.5-1 parts by weight of an antioxidant.

7. The EVA waterproof material according to claim 6, characterized in that: The antioxidant is a hindered phenol antioxidant and / or a phosphite antioxidant.

8. A method for preparing the EVA waterproof material according to any one of claims 1 to 7, characterized in that: The following steps are involved: After the components are uniformly mixed according to proportion, melt extrusion granulation is carried out to obtain EVA waterproof material.

9. The method for preparing the EVA waterproof material according to claim 8, characterized in that: The temperature of the melt extrusion is 180-210°C.

10. Application of the EVA waterproof material according to any one of claims 1 to 7 in a waterproof layer.